Review New Application using Interpolation and Polynomial ‎Approximation - Elbori, Abdalftah; Wafaa Abou zenad; Ali Albarki (AlQalam Journal of Medical and Applied Sciences, 2024)
This study analyses the mathematical structure of the interpolation to guarantee that the resulting function passes through all given data points. At the same time, polynomial approximation aims to find a polynomial function that closely matches the data but may not pass through all points and is typically determined using the least squares. Both methods have their advantages and are used in various fields, depending on the specific requirements of the problem at hand. The paper also explores the Lagrange Interpolation Error Theorem, providing insights into the accuracy and limitations of interpolation techniques. Understanding these methods and their error ata cteristiccs helps in selecting the appropriate approach for various practical applications. تحلل هذه الدراسة البنية الرياضية للتدخل لضمان مرور الدالة الناتجة عبر جميع نقاط البيانات المعطاة. وفي الوقت نفسه، يهدف التقريب متعدد الحدود إلى إيجاد دالة متعددة الحدود تتطابق بشكل وثيق مع البيانات، ولكنها قد لا تمر عبر جميع النقاط ويتم تحديدها عادةً باستخدام المربعات الصغرى. تتمتع كلتا الطريقتين بمزاياهما ويتم استخدامهما في مجالات مختلفة، اعتمادًا على المتطلبات المحددة للمشكلة المطروحة. كما يستكشف البحث نظرية خطأ التدخل لاغرانج، مما يوفر رؤى حول دقة وحدود تقنيات التدخل. يساعد فهم هذه الطرق وخصائص خطأها في اختيار النهج المناسب لمختلف التطبيقات العملية